2003
DOI: 10.1128/iai.71.11.6165-6170.2003
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Genes in Uninfected and Rickettsia -Infected Dermacentor variabilis Ticks as Assessed by Differential-Display PCR

Abstract: Ticks serve as both the vector and the reservoir for members of the spotted fever group rickettsiae. The molecular interaction(s) that results from this close relationship is largely unknown. To identify genetic factors associated with the tick response to rickettsial infection, we utilized differential-display PCR. The majority of upregulation appeared in the infected tissue. We cloned and sequenced 54 differentially expressed transcripts and compared the sequences to those in the GenBank database. Nine of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 32 publications
3
47
0
4
Order By: Relevance
“…Recent reports indicate that genes putatively functioning as receptor/adhesion and immune response effectors are differentially expressed in ovaries from D. variabilis ticks chronically infected with R. montanensis (26,28). Therefore, it was of interest to examine the transcriptional profiles of three important antimicrobial genes in response to rickettsial challenge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports indicate that genes putatively functioning as receptor/adhesion and immune response effectors are differentially expressed in ovaries from D. variabilis ticks chronically infected with R. montanensis (26,28). Therefore, it was of interest to examine the transcriptional profiles of three important antimicrobial genes in response to rickettsial challenge.…”
Section: Resultsmentioning
confidence: 99%
“…Of equal interest was the use of a differential display to parse the same experimental design for ovary-specific differentially expressed genes. Macaluso et al (26) found that Ena/ vasodilator-stimulated phosphoprotein-like protein, vacuolar ATPase, and ␣-catenin transcripts were all up-regulated in infected ovaries, reflecting the potential importance of these proteins for rickettsial entry and intra-and intercellular mobility.…”
Section: Vol 75 2007mentioning
confidence: 99%
“…We used standard PCR to amplify a fragment of the tick mitochondrial 16S rRNA gene using primers 16S+1 (5′-CTGCTCAATGATTTTTTAAATTGCTGT-3′) and 16S-1 (5′-GTCTGAACTCAGATCAAGT-3′) (Macaluso et al 2003, Nadolny et al 2011). PCR reactions were performed in 15 µL reaction volumes, with 0.05 U/µL Taq DNA Polymerase (BioPioneer Inc., San Diego, CA), 1 µM each primer, 1.5 mM MgCl 2 , 1X PCR buffer (Qiagen Inc., Valencia, CA) and 2 µL DNA template.…”
Section: Methodsmentioning
confidence: 99%
“…To confirm this possibility, semiquantitative RT-PCR was performed with the original samples of RNA, in situ and suspended, from three different experiments. Semiquantitative RT-PCR analysis has previously been used to confirm differences in gene expression (15,24,26). Specific primers were designed to analyze the levels of expression of the genes presented in Table 2.…”
Section: Bacterial Community Analysismentioning
confidence: 99%